Transverse Zeeman background correction method for air mercury measurement - 李传新 司福祺 刘文清 周海金 江宇 胡仁志 (Chinese physics B, 2014)
By utilizing a natural mercury lamp, the transverse Zeeman background correction method, which is used for trace mercury measurement in air, is studied. In this paper, a natural mercury lamp is used as a light source, and is placed in a 1.78-T magnetic field. The lamp emits two linearly polarized light beams σ± and π of 253.65-nm resonance line, which are used as bias light and absorbing light, respectively. A polarization modulation system is used to allow σ± and π light beams to pass through alternately with a certain frequency. A multipath optical cell with 12-m optical path is used to increase optical distance. Based on the system described above, the influence caused by UV absorbing gases, such as NO2, SO2, acetone, benzene, and O3, is analyzed. The results show that it may reduce the detection limit when the concentrations of these gases exceed 83.4 ppm, 20.3 ppm, 142.3 ppm, 0.85 ppm, and 0.55 ppm, respectively. The detection limit of the system is calculated and can achieve up to 1.44 ng/m3 in 10 minutes. Measurements on mercury sample gas and air are carded out, and the measured data are compared with the data of RA-915 mercury analyzer （Russia）. The result shows that the correlation coefficient reaches up to 0.967. The experimental results indicate that the transverse Zeeman background correction method can be used to quantify trace mercury in air with high-precision.